2014
DOI: 10.1002/path.4381
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastasis: demonstration that FOXP3 regulates CXCR4 expression and the response to CXCL12

Abstract: The X-linked transcription factor FOXP3 is expressed by epithelial cells of organs including the breast, where it is considered a tumour suppressor. The chemokine receptor CXCR4 also regulates the development of breast cancer by stimulating cell migration towards CXCL12-expressing sites of metastatic spread. During activation, human T cells show reciprocal regulation of FOXP3 and CXCR4. This study was designed to examine the role FOXP3 plays in metastatic breast cancer, with a particular focus on its potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…In contrast, specific knockdown of FOXP3 in normal breast epithelial cells increased HER2, SKP2, c-MYC and CXCR4 expression (37). These results suggest FOXP3 functions as a tumor suppressor in BC.…”
Section: Ccr7mentioning
confidence: 39%
See 1 more Smart Citation
“…In contrast, specific knockdown of FOXP3 in normal breast epithelial cells increased HER2, SKP2, c-MYC and CXCR4 expression (37). These results suggest FOXP3 functions as a tumor suppressor in BC.…”
Section: Ccr7mentioning
confidence: 39%
“…The subcellular location of a protein is related to function especially in the case of FOXP3, which as a transcription factor originally was believed to be limited to a nuclear location (37). In tumor cells, cytoplasmic localization has been explained by failure in translocation to the nucleus (35,38).…”
Section: Ccr7mentioning
confidence: 99%
“…Previous studies indicated that FOXP3 can reduce the migratory and invasive capacity of malignant ovarian cells by downregulating MMP-2 and uPA, as well as mTOR and NF-κB [15]. Another study in breast cancer showed that FOXP3 may regulate cancer invasion and metastasis by regulating the expression of chemokine receptors, such as CXCR4 [40, 41]. A study in gastric cancer revealed that FOXP3 is a tumor-suppressor that inhibits NFκB activity, and thereby inhibits COX2 expression [29].…”
Section: Discussionmentioning
confidence: 99%
“…26 Another example is metastasis of breast cancer cells to the lung, driven by SDF-1 and its receptor CXC chemokine receptor 4 (CXCR4). [27][28][29] Recently, exosome secretion was shown to enhance chemotaxis of neutrophils and macrophages. 21,30,31 However, the role of exosome secretion in cancer cell chemotaxis is unknown.…”
Section: Introductionmentioning
confidence: 99%